Desentralisasi yang Mengarah ke Sistem Federal dan Pengaruhnya Terhadap Pelaksanaan Fungsi Negara - Hendratno, Edie Toet (Indonesian Journal of International Law, 2007)
Article 18 Paragraph (5) of the 1945 Constitution of the Republic of Indonesia stipulates that the local administration (regional government) can implement autonomy as wide as possible, except for the administration affairs that are stipulated as the (central) government’s affair. This stipulation contains the principle of the transfer of the reserve of powers of the government to the local administration. The same goes with the decentralization policy in Act 22/1999 on Local Administration, as well as other legislations like the Act on Special Autonomy for Nanggroe Aceh Darusalam and Papua. They contain saome federal arrangement. The decentralization process that leads to the federal system influences the implementation of state functions.